IMPROVING SCIENTIFIC AND METHODOLOGICAL SUPPORT BASED ON THE INTEGRATION OF INNOVATIVE PEDAGOGICAL TECHNOLOGIES - Yulchiyeva Zulfiya Bakhodir kizi (Innovate Conferences, 2025)
The article will cover theoretical and practical aspects of improving scientific and methodological support based on the integration of innovative pedagogical technologies. The role of the harmonization of digital educational tools, interactive methods, a competency approach, STEAM and distance learning technologies in increasing educational quality is analyzed. Also, the advantages of the integrative approach, the impact on the qualifications of the teacher and the factors that ensure the effectiveness of the educational process are indicated.
Keywords: innovative technologies, integration, scientific and methodological support, digital education, competency approach, pedagogical methods, STEAM, distance education.